2016 IEEE Tenth International Conference on Research Challenges in Information Science (RCIS) 2016
DOI: 10.1109/rcis.2016.7549355
|View full text |Cite
|
Sign up to set email alerts
|

Enabling process mining on sensor data from smart products

Abstract: Abstract-In this paper we address the challenge of applying process mining to discover models of human behaviour from sensor data. This challenge is caused by a gap between sensor data and the event logs that are used as input for process mining techniques, so we provide a transformation approach to bridge this gap. As a result, besides the automatic discovery of process models, the transformed sensor data can also be used by various other process mining techniques, e.g. to identify differences between observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…In the current research, PM based on customer data focuses on process discovery. Van Eck et al [54] aim at discovering user behavior using sensor data gathered from a smart product. In their use case, they investigated the feeding process of a baby with a sensor-equipped bottle.…”
Section: Related Workmentioning
confidence: 99%
“…In the current research, PM based on customer data focuses on process discovery. Van Eck et al [54] aim at discovering user behavior using sensor data gathered from a smart product. In their use case, they investigated the feeding process of a baby with a sensor-equipped bottle.…”
Section: Related Workmentioning
confidence: 99%
“…In van Eck et al (2016), the authors translate continuous sensor data into higher-level events. The only input required is a minimal window size, in which the input sensor data needs to be segmented.…”
Section: Supervised Techniquesmentioning
confidence: 99%
“…Initial approaches can be found that apply process mining to raw data. For instance, a transformation approach is discussed by van Eck et al [35] applying process mining techniques to sensor data. The available approaches have in common that they intend to map sensor data to activities beforehand.…”
Section: Existing Work Related To Q1mentioning
confidence: 99%